Avaliação do efeito osteoindutivo do PDGF-BB associado a diferentes carreadores na regeneração óssea em cavidades cirurgicamente criadas - Oliveira, Júlio César Silva de [UNESP] (2015)
Objectives Extensive bone defects in maxillofacial region can be corrected with autograft, however the disadvantages of this type of therapy lead to the search for new bone substitutes. Thus, we evaluated the biological behavior and osteoinductive PDGF-BB associated with different carriers, by histological analysis and immunohistochemical histometric critical defects performed in rats calvaria. Materials and method 96 critical defects were created with 5 mm diameter calvaria of rats. Each defect was randomly divided into eight experimental groups (AUT, COA, TCP, TCP + PDGF, END, END + PDGF, BIO, BIO + PDGF), evaluated at 15 and 30 postoperative days for histomorphometry and immunohistochemistry. Results The results showed new bone formation in all groups, independent of postoperative time. At 30 days, the TCP group just did not differ from BIO group in the new bone formation (p = 0.1403). In none of the groups analyzed biomaterials, growth factor stimulated increase in bone formation (p > 0.05). Conclusion With the methodology used, the growth factor associated with the tested biomaterials did not induce new bone formation. Clinical relevance Based on these results, it is necessary to unravel the osteoblastic mechanisms in the early stages of bone healing and their outcome in the long term, so that the appropriate concentration of PDGF-BB may be well employed with the bone structure that most favors for maxillofacial reconstructions.